PEMBELAJARAN MODEL METODE KASUS (CASE METHOD) UNTUK MENINGKATKAN PEMBELAJARAN INOVASI MAHASISWA MATA KULIAH MANAJEMEN STRATEGIK - Adriani, Zulfina; Amin, Shofia; Rosita, Sry (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2023)
Strategic management is very important in managing an organization, because it can differentiate how well an organization achieves its performance, can face all forms of change and every decision provides benefits for various forms and types of profit-oriented organizations, government institutions, health and other organizations. other non-profits. Strategy is a process of implementing planning to achieve the organization's long-term goals by involving various existing resources. The Strategic Management course is a course designed to provide students with an understanding so they can implement a series of managerial decisions and actions in determining company performance in the long term. After students complete this strategic management course, students are expected to understand strategic management in terms of environmental observation, strategy formulation (strategic planning or long-term planning), strategy implementation, and evaluation/control. In addition, students are able to consider the implications of organizational strategy for the entire human resource system in the organization by translating organizational goals into specific resource management systems.Keywords: Case Methode, Management, Strategy.